Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Certainly! Let's tackle each part of this problem one step at a time.
### Part a) Find [tex]\( f(3) \)[/tex]
Given the function:
[tex]\[ f(x) = \frac{x^2 - 3}{2} \][/tex]
To find [tex]\( f(3) \)[/tex], substitute [tex]\( x = 3 \)[/tex] into the function:
[tex]\[ f(3) = \frac{3^2 - 3}{2} \][/tex]
[tex]\[ f(3) = \frac{9 - 3}{2} \][/tex]
[tex]\[ f(3) = \frac{6}{2} \][/tex]
[tex]\[ f(3) = 3 \][/tex]
So, [tex]\( f(3) = 3 \)[/tex].
### Part b) Find [tex]\( f^{-1}(x) \)[/tex]
To find the inverse function [tex]\( f^{-1}(x) \)[/tex], we start with the equation for [tex]\( f(x) \)[/tex] and solve for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex].
Start with:
[tex]\[ y = f(x) = \frac{x^2 - 3}{2} \][/tex]
Rearrange the equation to solve for [tex]\( x \)[/tex]:
[tex]\[ y = \frac{x^2 - 3}{2} \][/tex]
[tex]\[ 2y = x^2 - 3 \][/tex]
[tex]\[ x^2 = 2y + 3 \][/tex]
[tex]\[ x = \pm \sqrt{2y + 3} \][/tex]
So, the inverse function [tex]\( f^{-1}(x) \)[/tex] can be written as:
[tex]\[ f^{-1}(x) = \pm \sqrt{2x + 3} \][/tex]
### Part c) Find [tex]\( f^{-1}(11) \)[/tex]
Using the inverse function [tex]\( f^{-1}(x) \)[/tex]:
[tex]\[ f^{-1}(x) = \pm \sqrt{2x + 3} \][/tex]
Substitute [tex]\( x = 11 \)[/tex] into the inverse function:
[tex]\[ f^{-1}(11) = \pm \sqrt{2 \cdot 11 + 3} \][/tex]
[tex]\[ f^{-1}(11) = \pm \sqrt{22 + 3} \][/tex]
[tex]\[ f^{-1}(11) = \pm \sqrt{25} \][/tex]
[tex]\[ f^{-1}(11) = \pm 5 \][/tex]
Therefore, the solutions are:
[tex]\[ f^{-1}(11) = -5, 5 \][/tex]
### Summary
- a) [tex]\( f(3) = 3 \)[/tex]
- b) [tex]\( f^{-1}(x) = \pm \sqrt{2x + 3} \)[/tex]
- c) [tex]\( f^{-1}(11) = -5, 5 \)[/tex]
### Part a) Find [tex]\( f(3) \)[/tex]
Given the function:
[tex]\[ f(x) = \frac{x^2 - 3}{2} \][/tex]
To find [tex]\( f(3) \)[/tex], substitute [tex]\( x = 3 \)[/tex] into the function:
[tex]\[ f(3) = \frac{3^2 - 3}{2} \][/tex]
[tex]\[ f(3) = \frac{9 - 3}{2} \][/tex]
[tex]\[ f(3) = \frac{6}{2} \][/tex]
[tex]\[ f(3) = 3 \][/tex]
So, [tex]\( f(3) = 3 \)[/tex].
### Part b) Find [tex]\( f^{-1}(x) \)[/tex]
To find the inverse function [tex]\( f^{-1}(x) \)[/tex], we start with the equation for [tex]\( f(x) \)[/tex] and solve for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex].
Start with:
[tex]\[ y = f(x) = \frac{x^2 - 3}{2} \][/tex]
Rearrange the equation to solve for [tex]\( x \)[/tex]:
[tex]\[ y = \frac{x^2 - 3}{2} \][/tex]
[tex]\[ 2y = x^2 - 3 \][/tex]
[tex]\[ x^2 = 2y + 3 \][/tex]
[tex]\[ x = \pm \sqrt{2y + 3} \][/tex]
So, the inverse function [tex]\( f^{-1}(x) \)[/tex] can be written as:
[tex]\[ f^{-1}(x) = \pm \sqrt{2x + 3} \][/tex]
### Part c) Find [tex]\( f^{-1}(11) \)[/tex]
Using the inverse function [tex]\( f^{-1}(x) \)[/tex]:
[tex]\[ f^{-1}(x) = \pm \sqrt{2x + 3} \][/tex]
Substitute [tex]\( x = 11 \)[/tex] into the inverse function:
[tex]\[ f^{-1}(11) = \pm \sqrt{2 \cdot 11 + 3} \][/tex]
[tex]\[ f^{-1}(11) = \pm \sqrt{22 + 3} \][/tex]
[tex]\[ f^{-1}(11) = \pm \sqrt{25} \][/tex]
[tex]\[ f^{-1}(11) = \pm 5 \][/tex]
Therefore, the solutions are:
[tex]\[ f^{-1}(11) = -5, 5 \][/tex]
### Summary
- a) [tex]\( f(3) = 3 \)[/tex]
- b) [tex]\( f^{-1}(x) = \pm \sqrt{2x + 3} \)[/tex]
- c) [tex]\( f^{-1}(11) = -5, 5 \)[/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.